PENGGUNAAN METODE AKUMULASI SATUAN BAHANG UNTUK PENDUGAAN RENDEMEN TEBU MAKSIMUM - , Saryono
Abstract : Sugar cane cropping, usually has been done by Visual Method and Counting Daily Calender Method. The Rendemen (sugar consentrate) value that will be got by these methods can not be optimum. Growing Degree Day (GDD) indeks \"Heat Unit\" is total heat from effective heat accumulation that is obtained by basic temperature of the plant to subtract from average daily temperature. In 1992 till 1995, the value of GGD indeks of Madubaru PT. Yogyakarta sugar estate various about 1413,9 till 1663,7. The best equation of heat unit :effective degrees\" of this research is SB1 (GDD indeks 1) with least variation coefisient value (KK) 1,87%. From four time cropping is obtained average Rendemen equation to all variety are : Rl = 5,519 + 0,043411 H 0,00018 H2 R2 = 6,159 + 0,03774 H 0,0001 H2 R3 = 4,273 + 0,04348 H 0,00001 H2 R4 = 2,875 + 0,06961 H 0,00021 H2 (R = Rendemen and H = Daily period). The conclusion are by GDD indeks and Polinomial Regression orde 2 the rendemen to daily period can be obtained is the cropping done at the right time or not.